2012
DOI: 10.5267/j.msl.2012.06.030
|View full text |Cite
|
Sign up to set email alerts
|

The study of relationship between organizational structure and strategic knowledge management in Islamic Azad University, Kermanshah Branch

Abstract: The application of strategic knowledge management requires specific organization structure due to unique and particular characteristics of knowledge. In other words, by passing through industry age toward knowledge age, strategic knowledge management is considered by organizations dramatically and by considering this new competitive edge, universities should prepare an appropriate background for strategic knowledge management (encoding strategy and personalizing strategy). The primary purpose of this research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The other factors including management, knowledge measurement and change management were in lower levels of importance. Akbari et al (2012) discussed that implementation of strategic knowledge management need specific organization structure because of unique and particular characteristics of knowledge. In fact, by passing through industry age toward knowledge age, strategic knowledge management has been taken into account by organizations dramatically and by considering this new competitive edge, universities must prepare a suitable background for strategic knowledge management by encoding strategy and personalizing strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other factors including management, knowledge measurement and change management were in lower levels of importance. Akbari et al (2012) discussed that implementation of strategic knowledge management need specific organization structure because of unique and particular characteristics of knowledge. In fact, by passing through industry age toward knowledge age, strategic knowledge management has been taken into account by organizations dramatically and by considering this new competitive edge, universities must prepare a suitable background for strategic knowledge management by encoding strategy and personalizing strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, by passing through industry age toward knowledge age, strategic knowledge management has been taken into account by organizations dramatically and by considering this new competitive edge, universities must prepare a suitable background for strategic knowledge management by encoding strategy and personalizing strategy. Akbari et al (2012) investigated whether there was a meaningful relationship between organizational structure, in terms of recognition, focus and complexity, and strategic knowledge management, in terms of codification strategy and personalization strategy, in Azad University, Kermanshah. In this survey, organizational structure was studied as independent variables and strategic knowledge management was taken into account as dependent variables.…”
Section: Introductionmentioning
confidence: 99%
“…The other factors including management, knowledge measurement and change management were in lower levels of importance. Akbari et al (2012) explained strategic knowledge management as a necessity for some specific organization structure. Akbari et al (2012) studied whether there was any relationship between organizational structure, in terms of recognition, focus and complexity, and strategic knowledge management.…”
Section: Introductionmentioning
confidence: 99%
“…Akbari et al (2012) explained strategic knowledge management as a necessity for some specific organization structure. Akbari et al (2012) studied whether there was any relationship between organizational structure, in terms of recognition, focus and complexity, and strategic knowledge management. They demonstrated that there was a meaningful relationship between organizational structure and strategic knowledge management in their university case study.…”
Section: Introductionmentioning
confidence: 99%
“…They determined the relationship between entrepreneurship and knowledge management components using structural equation modeling and reported that knowledge content was number one priority followed by knowledge tools and concept of knowledge. Akbari et al (2012) explained that implementation of strategic KM needs specific organization structure due to unique and particular characteristics of knowledge. Akbari et al (2012), in other survey, tried to find out whether there was any meaningful relationship between organizational structure, in terms of recognition, focus and complexity, and strategic knowledge management, in terms of codification strategy and personalization strategy, in a private University.…”
Section: Introductionmentioning
confidence: 99%